Artemisia plant oil effectively reduces enteric methane emissionsin Sahiwal calves - KUMAR, ANKIT; DEVI, NISHU; CHAUDHARY, PARUL; NAIR, PRASANTH M; MAITI, SANJIT; MONDAL, GOUTAM (The Indian Journal of Animal Sciences, 2026)
Livestock sector significantly contributed to atmospheric greenhouse gas (GHG) leading to climate change. Several plants and their products can reduce the enteric methane emission from ruminant livestock. In the present study, the potential of Artemisia annua essential oil (EO) to reduce methane production in ruminants was investigated. In vitro trials with 0, 50, 100, 150, 200 and 250 ppm of essential oil supplementation in a 60:40 (roughage to concentrate) ratio revealed significant methane reduction at 50 ppm (20.90%) and 100 ppm (27.31%) with improved IVDMD and IVOMD (P0.05). Enteric methane emission (g/d) decreased significantly in T1 by 13.36% and in T2 by 10.83% compared to the control. Methane emissions (g/kg DMI) also decreased by 18.52% in T1 and 14.18% in T2 as compared to control. Artemisia annua essential oil at 50 and 100 ppm mitigated enteric methane while maintaining normal nutrient utilization and growth. Therefore, Artemisia annua EO may be an option to reduce enteric emission and sustainable dairy production.